Frailty as a risk marker of adverse lower urinary symptom outcomes in patients with benign prostatic hyperplasia undergoing transurethral resection of prostate - Ren, Xiang; Wang, Jing; Wang, Zhixian; Yin, Yisheng; Li, Xing; Tian, Yiqun; Guo, Zihao; Zeng, Xiaoyong (Frontiers in Medicine, 2023)
Purpose: Lower urinary symptoms (LUTS) may persist in a proportion of patients with benign prostatic hyperplasia (BPH) following transurethral resection of prostate (TURP), which is a major cause of reduced quality-of-life. We aimed to investigate the effect of frailty on LUTS in patients with BPH treated with TURP. Methods: We longitudinally evaluated LUTS and health-related quality-of-life (HRQOL) in patients with BPH treated with TURP from February 2019 and January 2022 using International Prostate Symptom Score (IPSS) and Short Form-8 (SF-8), respectively. Patients were divided into frail and non-frail groups according to the Fried phenotype (FP). The primary purpose was comparing the outcomes of LUTS and HRQOL between two groups. Secondary purposes were investigating the frailty as a preoperative predictor of postoperative adverse LUTS outcomes following TURP using logistic regression analysis. To reduce influences of selection bias and possible confounders, a 1:2 propensity score matching (PSM) was performed. Results: Of the 567 patients enrolled, 495 (87.3%) patients were non-frail (FP = 0-2), and the remaining 72 (12.7%) patients were classified into the frail group. There were no significant differences in body mass index (BMI), urine white blood cell (UWBC), creatinine, prostate-specific antigen (PSA) and prostate volume in the two groups at baseline (all P > 0.05). However, patients with frailty were older, higher comorbidity rates, lower peak flow rates and lower HRQOL. In the frail group, although LUTS and HRQOL at 6 months following TURP significantly improved compared to those at the baseline, it did not show significant improvement compared with the non-frail group (both P < 0.001). Moreover, multivariable logistic regression analysis demonstrated that preoperative frailty was significantly associated with poor LUTS improvement in both the entire cohort and PSM subset (both P < 0.05), whereas age and comorbidities were not after PSM analysis. Conclusion: In patients with frail or non-frail, TURP for BPH provides overall good results. However, frail individuals are at higher risk of postoperative adverse LUTS outcomes. Frailty has the potential to be a strong objective tool for risk stratification and should be considered during the perioperative evaluation.